«Життя як воно є»: соціокультурний контекст і методологічні принципи дослідження Саулом Боровим історії українського єврейства ХVІІ–ХVІІІ ст. - Гаухман, М. (Історіографічні дослідження в Україні, 2014)
Стаття присвячена дослідженню Саулом Боровим у 1930-х рр.
історії українського єврейства ХVІІ–ХVІІІ ст. Одеський історик
у період «культурної революції» здійснив методологічну переорієнтацію на основі радянського марксизму, що дозволило
йому задовольнити власний інтерес до дослідження контроверсійних тем україноюдаїки, розпочати вивчення біографії
лжемесії Сабатая Цві та переглянути єврейські сюжети ранньо-модерної історії України. The article deals with researches of the Ukrainian Jewry’s history
of ХVІІ–ХVІІІ centuries by Saul Borovoy in 1930th. The Odessa’s
historian in the period of the “cultural revolution” made the
methodological reorientation on the basis of Soviet Marxism, which
was spread among Soviet historians, because the “cultural revolution”
and Soviet Marxism allowed to abandon “methodological
nationalism” in historical investigation. This reorientation allowed
him to realise his own interest to rewriting Jewish history and to
formulate the idea of studying the biography of Sabbatai Tzevi in the
broad sociocultural context of ХVІІ century. This idea obligatory
needed to include Jewish aspects in Ukrainian historical process of
early modern epoch, which was done by Saul Borovoy in his articles and doctor thesis.